A Schiff-base cross-linked supramolecular polymer containing diiminophenol compartments and its interaction with copper(II) ions - Schmitt, Wolfgang; Gunnlaugsson, Thorfinnur (My University, 2018)
We report here the preparation of a Schiff-base linked organic polymer 1 based on linkages containing the potent supramolecular aggregator benzene-1,3,5-tricarboxamide, connected through 2,6-diiminophenol metal binding pockets into a cross-linked polymer. The morphological and physical properties of this material are studied using electron microscopy techniques, thermal analysis, NMR, fluorescence spectroscopy and gas adsorption studies. The interaction of the polymer 1 with CuII ions is then investigated by soaking the material with methanolic copper acetate solution, and studying the resulting aggregates using EDX microscopy and FTIR spectroscopy. A small-molecule model compound 2 is also prepared and crystallographically characterised to act as a spectroscopic comparison, providing strong evidence that 1 interacts with copper ions through a nucleation/seeding mechanism for the growth of microcrystalline copper acetate deposits, rather than via chemisorption of the copper ions within the diiminophenol binding pockets. Preliminary results suggest a similar mechanism for CoII adsorption, while ZnII ions exhibit a separate interaction mode.
PUBLISHED
Keywords: Benzene-1,3,5- tricarboxamide; Self-assembly; Supramolecular chemistry; Organic polymers; Schiff base